Effectiveness of cervical length screening by transvaginal sonography and use of progesterone for preventing preterm labour - Dhobale, Snehal S.; Satia, Meena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Incidence of preterm labour is about 6-15 % of pregnancies worldwide. It is major public health problem in terms of loss of life, long term disability, and health care cost both in developing and developed countries. The incidence of preterm births in India is estimated to be 11-14 % which means about 3 to 4 million preterm live births annually. Early identification of at risk pregnant women with timely referral will help to decrease the extreme prematurity rate, thereby reducing morbidity, mortality and will have a profound impact on societal and long-term public healthcare costs. So this study where vaginal progesterone was administered in women with short cervix detected by Transvaginal sonography to prevent preterm labour will be helpful in decreasing cases with preterm delivery and hence improve the perinatal outcome. Methods: It is prospective observational study in which 100 ANC patients who were registered at KEM Hospital a tertiary care centre in Mumbai in India at 16-24 weeks of gestation were studied to determine usefulness of 200 mg vaginal progesterone twice daily till 36 weeks in preventing preterm birth in those having cervical length 25mm or less. Results: Among 100 participants in this study, 48 (48%) were primigravida and 52 (52%) were multigravida. Out of 48% primigravida in the present study, preterm labour is prevented in 75% of women by the use of vaginal progesterone and out of 52% of multigravida, it is prevented in 71.2% of women. Conclusions: The study concluded that use of vaginal progesterone 200 mg in women with cervical length 25 mm or less measured by transvaginal sonography (as a good predictor of preterm labour) has useful effect in preventing preterm labour as well as associated neonatal mortality and morbidity. Neonatal survival is critically dependent on maturity of an infant and progressively increases with gestational age. Each day critically impacts on maturity and survival. Thus prevention and/or effective management of preterm labour will improve neonatal outcome and will have a profound impact on societal and long-term public healthcare costs.